Peningkatan pengetahuan ibu hamil tentang gingivitis melalui penyuluhan individual sebagai upaya pencegahan bayi berat lahir rendah (BBLR) di Gampong Kyee Leu Aceh Besar - Nuraskin, Cut Aja; Reca, Reca (Politeknik Kesehatan Kemenkes Aceh, 2024)
The effects of pregnancy on dental and oral health include pregnancy gingivitis caused by increased concentrations of the hormones estrogen and progesterone in the continuation of gingival inflammation which is considered to affect fetal growth both through systemic infections (hematogens) and increased inflammatory mediators that cause low birth weight and premature babies. This community service aims to provide practical information that can be applied directly by pregnant women in preventing and treating gingivitis. The method of community service will be given face to face. The targets are pregnant women and posyandu cadres, Aceh Besar PKK cadres consisting of 30 people. Community Service Results, Increased Knowledge about the importance of dental and oral hygiene during pregnancy increased by 40%, Increased Knowledge about gingivitis and pregnancy complications such as BBLR 45%, Increased Knowledge about techniques and Frequency of brushing teeth at least 2 times a day 40%, Increased Use of herbal mouthwash (cocoa extract) 55%. There is an increase in pregnant women's knowledge about dental and oral hygiene, and behavioral changes in maintaining oral hygiene. suggestion, it is important to carry out continuous training for health cadres, and continuous support from the government and health workers is needed.